Pengaruh Partisipasi Penyusunan Anggaran, Komitmen Organisasi, dan Motivasi terhadap Kinerja Manajerial - Nur Salma (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2020)
This research aims to understand and analyze the participation of the establishment of the budget, organization commitment and motivation of its effect on managerial performance on a body of financial management and its assets the city of bandar lampung. This study using samples from 64 respondents is the population employees at financial and assets management board of the area of a Bandar Lampung city as an object of research. Data collection method undertaken directly using data primary that is spreading the questionnaire to respondents.While the analysis used to know free variable influence (X1) budgeting participation, ( X2) organizations commitment and (X3) motivation on bound variables (Y) managerial performance is multivle regression linier analysis program spss 20. This research result indicates that using level significance 0.05 because the two sides so 2.5 % and n = 64 obtained f table of = 2,76. While f count seen of the output of sports data is 55,773 (f count > f table) and based on the f this concluded that simultaneously budgedting participation, organization commitment and motivation have had a positive impact and significant on managerial performance.Then with a significance 0.05 and n = 64 obtained t table of 2,0003, while t count of 2,084 to budgedting participation , 4,295 to organizations commitment and 2,409 to motivation ( t count > t table) and based on the t this inferred budgeting participation, organization commitment and motivation have had a positive impact and significant on managerial performance.